2008
DOI: 10.1016/j.cell.2008.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Organization of Hedgehog Is Essential for Long-Range Signaling

Abstract: Hedgehog (Hh) plays crucial roles in tissue-patterning and activates signaling in Patched (Ptc)-expressing cells. Paracrine signaling requires release and transport over many cell diameters away by a process that requires interaction with heparan sulfate proteoglycans (HSPGs). Here, we examine the organization of functional, fluorescently tagged variants in living cells by using optical imaging, FRET microscopy, and mutational studies guided by bioinformatics prediction. We find that cell-surface Hh forms subo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
162
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(167 citation statements)
references
References 39 publications
5
162
0
Order By: Relevance
“…Furthermore, a recent study has shown that Hh monomers can form nanoscale oligomers that are selectively enriched in visible clusters containing HSPGs [43]. The association of Hh oligomers with HSPG clusters promoted the dispatch of Hh for long-range transport (possibly via lipoprotein particles) and the activation of Hh target-gene expression in distant receiving cells [43]. However, enhanced binding to HS is not a common finding and was not demonstrated for the E131K mutant protein.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, a recent study has shown that Hh monomers can form nanoscale oligomers that are selectively enriched in visible clusters containing HSPGs [43]. The association of Hh oligomers with HSPG clusters promoted the dispatch of Hh for long-range transport (possibly via lipoprotein particles) and the activation of Hh target-gene expression in distant receiving cells [43]. However, enhanced binding to HS is not a common finding and was not demonstrated for the E131K mutant protein.…”
Section: Discussionmentioning
confidence: 98%
“…Studies have suggested that HSPGs can facilitate Hh movement by means of lipoprotein binding in the extracellular matrix and can antagonize PTC-mediated Hh sequestration, thereby promoting long-range movement [41,42]. Furthermore, a recent study has shown that Hh monomers can form nanoscale oligomers that are selectively enriched in visible clusters containing HSPGs [43]. The association of Hh oligomers with HSPG clusters promoted the dispatch of Hh for long-range transport (possibly via lipoprotein particles) and the activation of Hh target-gene expression in distant receiving cells [43].…”
Section: Discussionmentioning
confidence: 99%
“…ing (23), so it is unlikely that a biologically relevant filament would be incompatible with complex formation with positive regulators of the signaling pathway. The specific crystal lattice contact in the original ShhN structure that was postulated as a possible Hh oligomerization interface involves Arg 73 (Lys 132 in Drosophila HhN) (23). This interface buries only 180 Å 2 of surface area and does not occur in any other HhN-containing crystal structures, either alone or complexed with Ihog, CDOFn3, BOCFn3, or Hip (22,32,36,37) and thus seems unlikely to represent a conserved self-interaction among HhN molecules.…”
Section: Resultsmentioning
confidence: 99%
“…Studies with fluorescently labeled Hh provide evidence for both a "nanoscale" assembly of Hh proteins that depends on homo-oligomerization and a visible-light scale cluster that depends on interactions between Hh and heparin sulfate proteoglycans (23 We find that interactions between mammalian Hh proteins and CDO and BOC are conserved in nature, and systematic inspection of 14 different HhN-containing crystal lattices reveals no evidence for a conserved contact that may reflect a physiological self-interaction between Hh proteins. We also show that interactions between ShhN and CDOFn3 are diminished at low pH, suggesting that CDO and BOC will release bound Hh proteins in low pH environments.…”
mentioning
confidence: 84%
See 1 more Smart Citation